2014
DOI: 10.1108/mhsi-04-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a recovery college in a Scottish University

Abstract: Purpose – The purpose of this paper is to describe the establishment of the Dumfries and Galloway Wellness and Recovery College (The College) within the University of the West of Scotland. Design/methodology/approach – A narrative approach is taken to outline the project and justify its philosophy. Findings – Progress so far is outlined and the vision for the future is explained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…The Recovery Colleges Characterisation and Testing (RECOLLECT) Study is an NIHR-funded evaluation of Recovery Colleges (RCs), a new innovation which uses co-production and adult education approaches, rather than treatment, to support mental health recovery [ 34 , 35 ]. RCs involve the development of a culture of ‘emancipatory education’ [ 36 ] with an emphasis on ‘inclusivity and egalitarianism’ [ 37 ]. Emerging fidelity criteria are located in counter-point to the current mental health system [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Recovery Colleges Characterisation and Testing (RECOLLECT) Study is an NIHR-funded evaluation of Recovery Colleges (RCs), a new innovation which uses co-production and adult education approaches, rather than treatment, to support mental health recovery [ 34 , 35 ]. RCs involve the development of a culture of ‘emancipatory education’ [ 36 ] with an emphasis on ‘inclusivity and egalitarianism’ [ 37 ]. Emerging fidelity criteria are located in counter-point to the current mental health system [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first UK recovery college opened in 2010 in London [ 18 ], with nearly 40 others established since including in Norfolk, Nottingham, Scotland, Sussex, Manchester, as well as further afield in Ireland, Australia, Japan and Canada [ 19 ]. Narrative descriptions [ 20 , 21 ], psychiatrists’ perspectives [ 22 ] and evaluation data from recovery colleges have documented largely positive outcomes. These have included participants’ perspectives on what makes recovery colleges effective [ 23 ], their impact and changes in organizational practice [ 24 ], factors that support and hinder attendance [ 25 ], participants’ experience [ 26 ], and financial savings through reductions in service use [ 18 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, searches of the literature indicated that there were no published studies of arts based recovery college courses. Arts are mentioned in some studies [ 20 , 23 , 28 ], but not evaluated separately from other recovery college courses.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery colleges aim to change the relationship between people who use services and mental health professionals to one of partnership. The guiding philosophy of the college is to foster a student and tutor role, where lived experience is valued and inclusivity is promoted (McCaig et al, 2014). Co-working is emphasised in all aspects of college life, including joint organisation, decision making, curriculum design and quality control (McGregor et al, 2014;Meddings et al, 2014b).…”
Section: The Principles Of Recovery Collegesmentioning
confidence: 99%
“…The courses offered at recovery colleges are based on recognising and exploring people's difficulties such as sleep problems, depression and anxiety, and the development of self-management strategies. There is support to help people understand psychiatric diagnoses and ways to manage drug and alcohol misuse, as well as an emphasis on the core positive values of happiness and mindfulness (McCaig et al, 2014;Meddings et al, 2015).…”
Section: The Principles Of Recovery Collegesmentioning
confidence: 99%